ЗЕЛЛИГ САББЕТТАЙ ХАРРИС - Абдиназимов, Ш.Н. (SCIENCE and SOCIETY, 2022)
This article examines the life and scientific achievements of Zellig Sabbateia Harris, one of the prominent representatives of American linguistics. The role of Harris in the development of descriptive linguistics is shown. The contribution of the author to the improvement of the methods of scientific analysis, distributive, substituent methods, the method of discussive analysis, three-phase morphological analysis and ideas about the theory of morphemes is determined.
Keywords: descriptive linguistics; morpheme; distribution; segmentation; identification; substitution; principles of morpheme classification; discussive analysis